The Effectiveness of Picture Series in Improving Students’ Writing Skill at Mega Buana University - Tri Endar Yogi Setiadi Saputra (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2023)
This research has two variables, namely the students’ writing skill as independent variable and picture series as dependent variable. The aim of the research is to find out the effectiveness of picture series in improving students’ writing skill at Mega Buana University. The research applied Pre-Experimental method, where the students were given both pre test and post test. The population of this research is the Fourth Semester Students of Midwifery Study Program at Mega Buana University with the total of population are 42 students. The researcher chose 15 students as sample. The sample was taken by using purposive sampling technique. The result of this research showed the probability was 0.000 < 0.05. Based on this fact can be showed that H0 was rejected. Therefore there was different mean score of pre test and post test in this class. By looking at this result, can be understood that picture series was effective to improve students’ writing skill.